Romantic attachment, infertility-related stress, and positive body image of women dealing with infertility - Calvo, Vincenzo; Fusco, Chiara; Pellicelli, Camilla; Masaro, Chiara (Frontiers in Psychology, 2023)
Infertility is a condition that can affect the physical, emotional, social, and relational issues of each partner, both as individuals and within the couple. Women's bodies seem to assume a crucial relevance as part of the experience of infertility and its treatments. An extended body of literature supports the role of romantic attachment orientations in facing infertility-related stress. However, the association between romantic attachment orientations, infertility-related stress, and women's body image has not been explored. This cross-sectional study aimed to investigate the role of romantic attachment and infertility-related stress concerning positive body image in 113 women dealing with infertility. Data were analyzed with correlation and path analyses. Results showed that high levels of attachment anxiety, attachment avoidance, and infertility-related stress were negatively associated with positive body image. Path analyses indicated that positive body image may be directly associated with romantic attachment anxiety. The negative association of attachment avoidance with body image appeared to be mediated by infertility-related stress. Findings suggest that romantic attachment insecurities and infertility-related stress are significantly associated with a worsened body image in infertile women. Implications for future research are discussed.